Kompetisi dan Efisiensi Bank Umum di Indonesia Periode 2008 - 2013 - Yusuf Munawar (Center for Economic Studies Universitas Katolik Parahyangan, 2017)
There are two point of views regarding the relationship between competition and efficiency, namely SCP hypothesis and Efficient Structuree Hypothesis. By using the data of 107 Indonesian conventional banks within the period of 2008-2013, the obtained result supports the SCP Hypothesis where the competition level in the banking industry will affect the level of bank efficiency in Indonesia. The result of impulse response function shows that the more competitive banking industry, the more efficient the banks in Indonesia. Another conclusion of this research is the differences in efficiency indicators do not affect the conclusion about the relationship between competition and bank efficiency. Keywords: Bank, Competition, Efficiency, Indonesia